ANALISIS TINGKAT AKTIVITAS SEISMIK DAN KERAPUHAN BATUAN DI DATARAN PAPUA DAN SEKITARNYA PADA KEDALAMAN 0-60 KM: ANALYSIS OF SEISMIC ACTIVITY AND ROCK FRIABILITY LEVEL IN THE PAPUA LAND AND SURROUNDINGS AT A DEPTH OF 0-60 KM - Muhammad Irfan Fadilah; Imam Setiaji Ronoatmojo (Journal of Geoscience Engineering & Energy (JOGEE), 2022)
There is a meeting point of the oceanic plate, namely the Pacific Plate which is subducting under Papua and moving to the southwest at a speed of 120 mm/year, and the Australian Plate which is moving towards the Eurasian Plate and moving north at a rate of 70 mm/year. This condition causes the areas of Papua and West Papua to be shaken by many earthquakes. This research was conducted to analyze the rock friability level, as well as seismic activity in the study area, in order to minimize the damage caused by the earthquake. The data used is earthquake data from the United States Geological Survey (USGS) from 1971-2021 or within a period of 50 years, with a depth of 0-60 Km, with an earthquake magnitude of M 2 and moment tensor data, using the least squares method. In the research region, 372 earthquake spots have been discovered in the last 50 years.. The highest ai and bi values are at magnitude 7.95 with ai values of 0.028937 and bi values of 0.1661137. At magnitude 4.9, the lowest ai and bi values are ai values 0.028927 and bi values 0.1660554. The number of earthquake frequencies in the area influences the value of ai (seismic activity), and the magnitude and seismic activity in the area influence the value of bi (rock friability level).Keywords : Papua, Seismic Activity, Rock Friability